PENGEMBANGAN MULTIMEDIA INTERAKTIF PADA PEMBELAJARAN RESENSI UNTUK PESERTA DIDIK KELAS XI SMAN 2 BANJARMASIN - Noor Asiah; Sainul Hermawan; Ahsani Taqwiem (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2024)
This study aims to describe the needs of students, the feasibility of interactive multimedia, and students' responses to interactive multimedia review text. This study used the Research and Development (R&D) method, with a 4-D research model consisting of define, design, develop, and disseminate stages. The results of this study indicate that 100% of class XI students at SMAN 2 Banjarmasin have a high level of need and are interested in using interactive multimedia in learning review texts. Through the research results it is known that the interactive multimedia that has been developed is rated